Pulmonary complications of immune checkpoint inhibitors in patients with nonsmall cell lung cancer. (9th October 2019) - Cadranel, Jacques; Canellas, Anthony; Matton, Lise; Darrason, Marie; Parrot, Antoine; Naccache, Jean-Marc; Lavolé, Armelle; Ruppert, Anne-Marie; Fallet, Vincent
Immune checkpoint inhibitor-related pneumonitis (ICI-P) during cancer treatment is rarely observed (<5%). ICI-P is more often observed in patients with nonsmall cell lung cancer (NSCLC) than in those with other cancers. Likewise, it is more common in those receiving programmed cell death (PD)-1/PD-1 ligand inhibitors rather than cytotoxic T-lymphocyte antigen (CTLA)-4 inhibitors alone. The frequency of ICI-P is higher when anti-PD-1 and anti-CTLA-4 are administered concomitantly. Despite the low fatality rate (≈13%), ICI-P is the leading cause of ICI-related deaths. This narrative review focuses on the epidemiology, clinical and radiological presentation and prognosis of ICI-P occurring in patients, especially those with advanced NSCLC. Emphasis is placed on the differences in terms of frequency or clinical picture observed depending on whether the ICI is used as monotherapy or in combination with another ICI or chemotherapy. Other pulmonary complications observed in cancer patients, yet not necessarily immune-related, are reviewed, such as sarcoid-like granulomatosis, tuberculosis or other infections. A proposal for pragmatic management, including differential diagnosis and therapeutic strategies, is presented, based on the ICI-P series reported in the literature and published guidelines. Immune checkpoint inhibitor-related pneumonitis (ICI-P) is rare. Despite a low fatality rate, it is the leading cause of death in relation to ICIs. It is crucial to recognise and manage ICI-P by stopping immunotherapy and quickly starting corticosteroids. http://bit.ly/2Ldsp3n